Climate Change in the Wine Sector of an Ultra-Peripheral European Region: A Case Study - Alonso, Abel; Liu, Yi (Taylor & Francis Inc, 2013)
This study examines climate change from the perspective of small winery operators in an ultra-peripheral European region. Most respondents in this study refer to changes in the last decades, including warm weather patterns that are pushing harvests earlier in the year. Such changes are having an impact on the final wine product, as alcohol volume has increased in some wines. Despite these new challenges, given growers' limitations of land space and resources, only the fewest growers are implementing strategies to minimize such impacts. Implications of the findings and future research avenues concerning climate change in the region are discussed.